Key wheat GRF genes constraining wheat tillering of mutant dmc - Zhang,Jing; Li,Junchang; Ni,Yongjing; Jiang,Yumei; Jiao,Zhixin; Li,Huijuan; Wang,Ting; Zhang,Peipei; Han,Mengyao; Li,Lei; Liu,Hongjie; Li,Qiaoyun; et al. (PeerJ, 2021)
Tillering is a key agronomy trait for wheat (Triticum aestivum L.) production. Previously, we have reported a dwarf-monoculm wheat mutant (dmc) obtained from cultivar Guomai 301 (wild type, WT), and found growth regulating factors (GRFs) playing important roles in regulating wheat tillering. This study is to systematically investigate the roles of all the wheat GRFs (T. aestivum GRFs, TaGRFs) in regulating tillering, and screen out the key regulators. A total of 30 TaGRFs were identified and their physicochemical properties, gene structures, conserved domains, phylogenetic relationships and tissue expression profiles were analyzed. The expression levels of all the TaGRFs were significantly lower in dmc than those in WT at early tillering stage, and the abnormal expressions of TaGRF2-7(A, B, D), TaGRF5-7D, TaGRF10-6(A, B, D) and TaGRF11-2A were major causes constraining the tillering of dmc. The transcriptions of TaGRFs were significantly affected by exogenous indole acetic acid (IAA) and gibberellin acid (GA3) applications, which suggested that TaGRFs as well as IAA, GA signaling were involved in controlling wheat tillering. This study provided valuable clues for functional characterization of GRF genes in wheat.
Keywords: Wheat (Triticum aestivum L.); Tillering; Growth regulating factor; Expression profiles; IAA; GA